In A World Of Your Own- Pavilion of Bahrain/ (3aj YGde ef UfYc(B- (3LfGM eedcI GdHMQjf (BPavilion of Bahrains : 55th International Art Exhibition- La Biennale di Venezia 2014 - Enders-Bhatia, Melissa; Flouty, Dr. Elie; Haji, Mariam; Malullah, Waheeda; Zakharia, Camille; (3O(B. (3Ejdj adhWjs; (3ejdjSG EfOQR HgGJjGs (Ministry of Culture, Kingdom of Bahrain, 2013)
Artists: Mariam Haji, Waheeda Malullah, Camille Zakharia
English; Arabic
Keywords: N4390-5098 Visual Arts- Exhibitions; Pavilion catalog; Bahrain